Varietal Screening of Radish Genotypes Against Alternaria Leaf Spot (Alternaria raphani) at Western Nepal - Kavita Adhikari; Chiranjivi Sharma; Anju Karki; Isha Budha Magar; Radhika Chand; Sajana Gharti Magar (Turkish Journal of Agriculture: Food Science and Technology)
Paucity of knowledge on resistant variety, high yield loss ranging from 32- 57% and dearth of knowledge on management of Alternaria leaf spot has been the major concerns in radish production in the world. Our study will aid in multiplication and standardization of the germane variety of radish resistant to Alternaria leaf spot disease so as to escalate the production, productivity, and the competitiveness in the domestic as well as in the international market. Hence, this experiment was rendered to screen the radish genotypes against Alternaria leaf spot disease in Western Nepal in 2021. Seven genotypes namely Sparkle white F1 hybrid, Korean cross, Palak-patta 35, Pyuthane red, 40 days, Geeta 33, and Mino early were used as the treatment and experiment was laid out in one factorial RCBD design. Each treatment was assigned with 8 plants for observation with 3 replications per treatment. Parameters like days to appearance of disease, incidence of disease on seedling, disease severity (3 scorings), mean score of disease, mean AUDPC and reaction of genotypes were measured during the experiment. Our study unveiled highly significant result for the days to appearance of disease, disease severity, mean score of disease and AUDPC among the genotypes of radish. Alternaria leaf spot first appeared in Pyuthane red (18.33 days) while appeared late in Mino early. Disease severity was found harsh in 40 days at each scoring (57.33, 64.67 and 70.33 respectively); on the contrary severity was minor in Sparkle white at each scoring (26.67, 35 and 44.17 respectively). Similarly, the highest MDS (3.4) and AUDPC (449.8) was found in 40 days, whereas the lowest MDS (1.7) and AUDPC (246.5) was observed in Sparkle white. Ultimately, it is contended that 40 days was found to be moderately susceptible variety while other varieties were found to be moderately resistant.